Removal of tetracycline from contaminated water by Moringa oleifera seed preparations - Santos, Andréa F S (Environmental technology, 2016)
The aim of this study was to evaluate tetracycline antibiotic (TA) removal from contaminated water by Moringa oleifera seed preparations. The composition of synthetic water approximate river natural contaminated water and TA simulated its presence as an emerging pollutant. Interactions between TA and protein preparations (extract; fraction and lectin) were also evaluated. TA was determined by solid-phase extraction followed by high-performance liquid chromatography-mass spectrometry. Moringa extract and flour removed TA from water. The extract removed TA in all concentrations, and better removal (40%) was obtained with 40 mg L(-1); seed flour (particles < 5 mm), 1.25 and 2.50 g L(-1) removed 28% and 29% of tetracycline, respectively; particles > 5 mm (0.50 g L(-1)) removed 55% of antibiotic. Interactions between TA and seed preparations were assayed by haemagglutinating activity (HA). Specific HA (SHA) of extract (pH 7) was abolished with tetracycline (5 mg L(-1)); fraction (75%) and lectin HA (97%) were inhibited with TA. Extract SHA decreased by 75% at pH 8. Zeta potential (ZP) of extract 700 mg L(-1) and tetracycline 50 mg L(-1) , pH range 5-8, showed different results. Extract ZP was more negative (-10.73 to -16.00 mV) than tetracycline ZP (-0.27 to -20.15 mV); ZP difference was greater in pH 8. The focus of this study was achieved since Moringa preparations removed TA from water and compounds interacting with tetracycline involved at least lectin-binding sites. This is a natural process, which do not promote environmental damage